The Waterberg project, Limpopo province, South Africa - Huthmann, Florian Marius (My University, 2018)
The Waterberg deposit is located north of the Northern Lobe of the Bushveld Complex in South Africa and represents a large, high-grade, new platinum-group element (PGE) discovery. The northeast-oriented lobate arc of ma c to ultrama c rocks extends 24 km from the previously known outcrop of Bushveld rocks. Laser ablation ICP-MS zircon U/Pb geochronology has returned ages of 2059 ± 3 and 2053 ± 5 Ma for the intrusion, ages that are within error of previously published ages for the Bushveld Complex of 2.056 Ga. It is therefore proven that the Bushveld Complex extends further to the north than previously thought. Based on laser ablation ICP-MS zircon U/Pb geochronology, detrital zircons extracted from the sedimentary rocks unconformably overlying the succession have a maximum depositional age of 2045 Ma and abundant peaks of Archean age. It may be argued that the Bushveld Complex now reaching to the Palala Shear Zone to the north indicates that assembly of the Kaapvaal and Zimbabwe Cratons only took place around 2.0 Ga. In detail, theWaterberg succession consists of a basal Ultrama c Sequence of harzburgite and feldspathic pyroxenite, overlain by the Troctolite-Gabbronorite-Anorthosite Sequence and locally Upper Zone, comprising magnetite gabbronorite and gabbro. Logging and geochemical data demonstrate that all samples represent ultrama c to gabbroic cumulate rocks dominated by varying proportions of olivine, plagioclase, clinopyroxene, and orthopyroxene. Mineralization occurs in the T and F Zones located just below the Upper Zone and in the Ultrama c Sequence, respectively. The Waterberg Project is an outstanding discovery with an indicated mineral resource of 25 Moz Pt+Pd+Rh+Au. Detailed geochemistry for the the lower mineralized F-Zone of the deposit indicates that although the Northern Lobe and the Waterberg Project share many geochemical features, there are also signi cant di erences. Sr isotopic data for plagioclase of the succession are di erent from values reported for the Northern Lobe of the Bushveld Complex. Together with geochemical data, the isotopic analyses suggest that a separate magmatic basin exists in the far northern Bushveld Complex. That is, although both intrusions are roughly coeval, the Waterberg succession was at least partially separated from the Northern Lobe and evolved independently. In summary, the Waterberg Project represents a highly mineralized Bushveld Complex-age succession sharing geological characteristics with the Northern Lobe. There are also clear di erences, however, and the two areas cannot be directly linked. Therefore, the project area is interpreted to represent a separate magmatic basin from the Northern Lobe, that is likely to include the rocks at the very northern end of the Northern Lobe of the Bushveld Complex. The results of this work have been published in four scienti c articles and presented at four academic conferences.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy School of Geosciences, University of the Witwatersrand, 2018